Urinary excretion of IGFBP-1 and -3 correlates with disease activity and differentiates focal segmental glomerulosclerosis and minimal change disease - Worthmann, Kirstin; Peters, Imke; Kuempers, Philipp; Saleem, Moin; Becker, Jan U.; Agustian, Putri A.; Achenbach, Johannes; Haller, Hermann; Schiffer, Mario (Growth Factors, 2010)
The glomerular microenvironment is influenced by circulating growth factors that are filtered from the blood stream and pass the glomerular filtration barrier. In this study, we wanted to explore the role of IGF-binding proteins (IGFBPs) in two diseases that concern podocytes. We analyzed glomerular expression and urinary excretion of IGFBP-1, -2, and -3 in patients with focal segmental glomerulosclerosis (FSGS) or minimal change disease (MCD). We found that patients with active FSGS excrete high amounts of podocalyxin positive cells as well as IGFBP-1 and -3. In human podocytes, we can induce mRNA expression of IGFBP-3 in response to TGF-β and in human microvascular endothelial cells expression of IGFBP-1 and -3 in response to TGF-β and Bradykinin. We conclude that the local expression of IGFBPs in podocytes and endothelial cells might contribute to the pathogenesis of glomerular disease and that IGFBP-1 and -3 are potential non-invasive markers of FSGS. © 2010 Informa UK Ltd.
CRIS-Team Scopus Importer:2020-11-12
Keywords: FSGS; IGFBP; Podocyte; TGF-β